Monetary union enlargement and international trade - Marchesiani, Alessandro (2007)
This paper studies the effects of monetary union enlargement on international trade in a three-country (two incumbent countries and an acceding country) search monetary model. It is shown that, the enlargement of a monetary union is expected to increase international trade and thus be Pareto improving, but may result in trade reduction if too much money is issued, and the degree of integration between the ICs is too high relative to integration with the AC.